17q12 deletion and duplication syndrome in Denmark—A clinical cohort of 38 patients and review of the literature. Issue 11 (13th July 2016) - Rasmussen, Maria; Vestergaard, Else Marie; Graakjaer, Jesper; Petkov, Yanko; Bache, Iben; Fagerberg, Christina; Kibæk, Maria; Svaneby, Dea; Petersen, Olav Bjørn; Brasch‐Andersen, Charlotte; Sunde, Lone
Abstract : 17q12 deletions and duplications are two distinct, recurrent chromosomal aberrations usually diagnosed by chromosomal microarray analysis (CMA). The aberrations encompass the genes, HNF1B, LHX1, and ACACA, among others. We here describe a large national cohort of 12 phenotyped patients with 17q12 deletions and 26 phenotyped patients with 17q12 duplications. The total cohort includes 19 index patients and 19 family members. We also reviewed the literature in order to further improve the basis for the counseling. We emphasize that renal disease, learning disability, behavioral abnormalities, epilepsy, autism, schizophrenia, structural brain abnormalities, facial dysmorphism, and joint laxity are features seen in both the 17q12 deletion syndrome and the reciprocal 17q12 duplication syndrome; and we extend the list of features seen in both patient categories to include strabismus, esophageal defects, and duodenal atresia. Delayed language development, learning disability, kidney involvement, and eye dysmorphism and strabismus were the most consistently shared features among patients with 17q12 deletion. Patients with 17q12 duplications were characterized by an extremely wide phenotypic spectrum, including a variable degree of learning disabilities, delayed language development, delayed motor milestones, and a broad range of psychiatric and neurological features. This patient group also included adults achieving an academic degree. Assessing index patients and non‐index patients separately, our observations illustrate that an overall milder disease burden is seen, in particular in patients with 17q12 duplications who are ascertained on the duplication rather than the phenotype. This evidence may be useful in prenatal counseling. © 2016 Wiley Periodicals, Inc.